2021
DOI: 10.1002/adma.202007344
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understandings into Complete Reconstruction of Precatalysts: Synthesis, Applications, and Characterizations

Abstract: Reconstruction induced by external environment (such as applied voltage bias and test electrolytes) changes catalyst component and catalytic behaviors. Investigations of complete reconstruction in energy conversion recently receive intensive attention, which promote the targeted design of top‐performance materials with maximum component utilization and good stability. However, the advantages of complete reconstruction, its design strategies, and extensive applications have not achieved the profound understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
220
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(221 citation statements)
references
References 244 publications
(313 reference statements)
1
220
0
Order By: Relevance
“…Recent research on the activity of the HER and oxygen evolution reaction (OER) has suggested that the in situ reconstructed surface of catalysts under electrochemical conditions provides intrinsic active sites for high catalytic activities [ 30 ]. For example, Liu et al discovered that phosphides derived from CoFeO@ black phosphorus (BP) formed during HER catalysis [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the activity of the HER and oxygen evolution reaction (OER) has suggested that the in situ reconstructed surface of catalysts under electrochemical conditions provides intrinsic active sites for high catalytic activities [ 30 ]. For example, Liu et al discovered that phosphides derived from CoFeO@ black phosphorus (BP) formed during HER catalysis [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worth mentioning that the as-obtained 3D heterostructure exhibits multi-level porosities and open channels, which are in favor of the effective solution permeability and gas release for electrocatalytic reactions. 21 The as-obtained Co@NCNT sub-arrays can act as a physical buffer to strengthen the robustness of the entire heterostructure, which is beneficial for the subsequent exploration of dissolution and self-reconstruction mechanisms with structural integrity.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic equilibria of redeposition, polymerization, and reduction evolution on the surface promote the formation of active species and maximize the component utilization, improving the efficiency of alkaline HER activity with long-term stability. 21…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some studies have reported that the reconstruction that occurs on catalytic materials is irreversible. [41] Due to the complexity of electrocatalysis,m any factors are likely to affect the reversibility of structural evolution. Even for the same type of material and the same reaction, the difference in the electrolytes and the catalyst surface will also [37] with permission.C opyright 2020, Nature Publishing Group.…”
Section: Angewandte Chemiementioning
confidence: 99%